A COMPARISON OF METHODS OF DETERMINING LONG-TERM RESISTANCE TO DISPLACEMENT ALONG FROZEN SURFACES - Haofen U. (My University, 1996)
Long-term resistance to displacement along frozen surfaces is an important characteristic of the strength of frozen ground. A knowledge of the value of this characteristic is necessary when calculating the load-carrying capacity of frozen foundations. The paper compares two laboratory methods of testing resistance to displacement on frozen surfaces: pressing model posts frozen into the ground; and displacing a fragment of the foundation frozen with the ground. Various equations for calculating the long-term strength of frozen ground were also tested. It was shown that the loading regime influences the value of long-term resistance to displacement on frozen surfaces.